Racial and ethnic differences in subclinical myocardial function: the Multi-Ethnic Study of Atherosclerosis. Issue 5 (21st January 2011) - Fernandes, Verônica Rolim S; Cheng, Susan; Cheng, Yu-Jen; Rosen, Boaz; Agarwal, Sachin; McClelland, Robyn L; Bluemke, David A; Lima, João A C
Abstract : Background: Racial/ethnic differences in the incidence and severity of heart failure (HF) are not well understood, but may be related to pre-existing variations in myocardial function. Objective: To examine racial/ethnic differences in regional myocardial function among asymptomatic individuals free of known cardiovascular disease. Design, setting and patients: The Multi-Ethnic Study of Atherosclerosis is a prospective, observational study of individuals without baseline cardiovascular disease, representing four major racial/ethnic groups. A total of 1099 study participants underwent cardiac MRI with tissue tagging; for each study, peak systolic strain (Ecc) and strain rate (SRs) were determined in four left ventricular (LV) regions. Main outcome measures: Multiple linear regression was used to analyse the relationship between race/ethnicity and regional strain (Ecc and SRs) while adjusting for cardiovascular risk factors. Results: Compared with other racial/ethnic groups, Chinese-Americans had the greatest magnitude of Ecc in a majority of LV regions (−19.60±3.78, p<0.05); Chinese-Americans also had the greatest absolute values for SRs in all regions, reflecting higher rate of systolic contraction (−2.01±0.76, p<0.05). Conversely, African-Americans had the lowest Ecc values (−17.50±4.00, p<0.05) in the majority of wall regions while Hispanics demonstrated the lowest rate of contractility in all wall regions (−1.44±0.50, p≤0.001) in comparison with the other racial/ethnic groups. These race-based differences remained significant in the majority of LV wall regions after adjusting for multiple variables, including hypertension and LV mass. Conclusions: Important race-based differences in regional LV systolic function in a large cohort of asymptomatic individuals have been demonstrated. Further research is needed to investigate the possible mechanisms related to the race/ethnicity-based variations found in this study.